The Sigma-1 Receptor as a Atypical Kv1.2 Auxiliary Subunit - Abraham, Madelyn Jean (Université d'Ottawa / University of Ottawa, 2018)
Delayed-rectifier potassium channels comprised of the Kv1.2 subunit are critical in maintaining appropriate neuronal excitability and determining the threshold for action potential firing. This is attributed in part to the interaction of the Kv1.2 subunit with an unidentified molecule that confers bimodal channel activation gating, allowing neurons to adapt to repetitive trains of stimulation and protecting against hyperexcitability. It is well established that the Sigma-1 receptor (Sig-1R) regulates members of the Shaker K+ channel family at baseline and upon Sig-1R ligand-activation. While an interaction between Kv1.2 and Sig-1R has been previously demonstrated, the biophysical nature of this interaction has not been elucidated. We hypothesized that Sig-1R may regulate the Kv1.2 biophysical properties and may further act as the unidentified modulator of Kv1.2 activation gating. To explore the interaction between Kv1.2 and Sig-1R, whole-cell voltage-clamp electrophysiology and apFRET imaging experiments were performed in recombinant HEK293 cells transiently transfected with Kv1.2 and Sig-1R. It was found that ligand-activation of Sig-1R decreases Kv1.2 current amplitude, likely due to a ligand-dependent change in Sig-1R activity rather than increased association of Sig-1R with Kv1.2. Further, we show that Sig-1R interacts with Kv1.2 in baseline conditions to modulate bimodal activation gating. We show that Sig-1R modulation of Kv1.2 is abolished both in the presence of Kvβ2, a known auxiliary subunit of Kv1.2, and following expression of the Sig-1R mutation underlying ALS16 (Sig-1R-E102Q). These data respectively suggest that Kvβ2 physically occludes the interaction of the Sig-1R with Kv1.2, and that E102 may be a residue critical for efficient Sig-1R modulation of Kv1.2. Taken together, this data provides novel insights regarding the modulation of neuronal delayed-rectifier potassium channels by Sig-1R. This work provides a new role for Sig-1R in the regulation of neuronal excitability and introduces a mechanism of pathophysiology in Sig-1R dysfunction.
Keywords: Sigma-1 receptor; Kv1.2; amytrophic lateral sclerosis; KvB2; electrophysiology; apFRET